Development of a mango-flavored sports drink - Baguio, Oscar Vicente Martinez
The general objective of the study was to develop a sports drink utilizing mango flavor. The first phase of the study dealt with the incorporation of artificial mango flavor into a suggested sports drink basal medium. Pre-test concentrations of artifical mango flavor including 0.00, 0.04, 0.06, and 0.88% (wt/v) flavor to basal medium where incorporated to the suggested basal medium and subjected to a sensory analysis. These test concentrations where within the limits recommended by Firminich, Incorporated which was 0.04% - 0.10%. Due to an overall low ratings od the initial sensory testings, and comments like the test beverages being too sweet or sour, modifications in the suggested basal medium was done. Modifications on the basal medium involved changing the amounts of sugar and citric acid. The 18% original total sugar concentration by volume of basal medium was changed to 6% since most commercial sports drinks are reported to contain only 6-8% sugar. Citric acid level was also decreased to 7.50 grams to compensated the change in sugar concentration. Results of the physico-chemical tests on the modified basal medium recorded the following: a pH value of 4.8, a TSS of 5.80°Brix, and a titratable acidity of 0.23%, expressed as citric acid. The original basal medium had a pH of 2.0, TSS of 18.0°Brix, and 1.10% TA. The third phase of the study involved incorporation of the same artificial mango flavor into the modified basal medium using test concentrations 0.00, 0.01, 0.02, and 0.03% (wt/v) flavor to basal medium. Consumer acceptability test results still showed low acceptability ratings, this time due to a medicine-like flavor basically attributed to the artificial flavor. Natural mango, in the form of puree, was therefore incorporated into the modified basal medium as substitute to the artificial mango flavor. mango puree was added to the modified basal medium at 0, 4, 5, and 6% testy concentrations (wt/v) flavor to basal medium. The 5% test mango flavor concentration was found to be the most acceptable and was described as having a perceptible mango aroma, slightly weak flavor strength, slightly weak level of sweetness, and an ideal level of sourness, tartness, and aftertaste. General acceptability rating was "like moderately". The fourth phase of the study dealt with the incorporation of an appropriated mango color to the mango-flavored sports drink. Using the 1 to 10 range of colors from the Roche color fan, a preliminary test resulted to the selection of Roche colors 5, 6, and 7 and were then simulated in the mango-flavored sports drink with McCormick Yellow food color. Roche colors 5, 6, and 7 had equivalent concentrations of 0.08, 0.10, and 0.15% (v/v) yellow food color to natural mango-flavored sports drink, respectively. The consumer acceptability test characterized the natural mango-flavored sports drink with 0.10% color concentration as the most acceptable and was characterized as having a light yellow orange color, perceptible mango aroma, slightly weak level of sweetness, and an ideal level of flavor strength, sourness, tartness, and aftertaste. General acceptability was "like moderately". The fifth phase involved storage stability of the formulated natural mango-flavored and light-yellow orange-colored sports drink. Samples of the sports drink were stored at 5°C and 28°C in 250-ml glass bottles. Physico-chemical and microbiological tests were performed every 3 d for a 15-fay storage period. The changes in pH, TSS, and %TA values of stored samples at 28°C were significantly different at 5% level of significance during the 15 d storage period. No significant difference was found in the physico-chemical test values for samples stored at 5°C for 15 d. Paired difference tests showed that there was a significant difference between pH, TSS, and %TA values stored at 5°C and 28°C from the 3rd d to 15th d of storage. At 0-day storage, the samples recorded had a pH of 4.8, TSS of 6.01°brix, and 0.26% TA. After 15 days of storage, samples stored at 5°C had a pH of 4.7, TSS of 6.0°Brix and 0.26% TA. Physico-chemical test results for samples stored at 28°C were: a pH of 4.3, 5.90°Brix and 0.38% TA. Product deterioration of samples stored in both test storage temperatures was attributed to the presence of lactic acid bacteria. Microbiological examination results, however showed TPC counts <10 cfu/ml during the test 15-day period. Use of a microbial assay more specific for isolation of lactic acid bacteria was recommended. Cost analysis of the formulated natural mango-flavored and light yellow orange-colored sports drink showed that the actual cost for its production was P10.55/250 ml glass bottle. A 10% mark-up would give a suggested retail price of 11.55/bottle. An 8.74% savings would be incurred against the leading comme